On scrambling in Turkish - Akan, Tamer. (Thesis (M.A.)-Bogazici University. Institute for Graduate Studies in Social Sciences, 2009., 2009)
This thesis aims to investigate the nature of the scrambling phenomenon in Turkish under the assumptions of minimalist program, which is the last phase of generative grammar. It focuses on the type of movement observed in scrambling in Turkish, namely A vs A-bar movement, the landing sites for both clause-internal and inter-clausal scrambling, the distance between the source and the landing site of the movement, the direction of movement and similarities and asymmetries between leftward and rightward scrambling. The canonical word order is considered to be SOV for Turkish. However, the application of certain movement operations may yield six different word orders (SOV, SVO, OSV, OVS, VSO, VOS), which indicates that Turkish is a scrambling language. Scrambling, which was first defined as free word order, is seen as a result of totally optional movement operations by some linguists and as a result of certain obligatory movement operations by some others. With respect to the nature of scrambling in Turkish, it has been argued that it is an instance of A-bar movement. Contrary to this view, it has been argued that clause-internal scrambling is an instance of both A-movement and A-bar movement. In this thesis, it is argued that scrambling is compatible with the last resort principle of the minimalist program. Based on the arguments on the syntactic properties exhibited by the scrambled constituents, it is claimed that scrambling to both pre-verbal position and post-verbal position involves A-bar movement. The driving force of movement is argued to be information structure, which feeds syntax. Also, it is claimed that different types of focus play crucial role in scrambling phenomenon in Turkish. This kind of an analysis provides indirect support for the analysis where it is also argued that scrambling must be seen as Abar movement. Thus, it follows that scrambling is a feature driven operation, indicating that it is a syntactic operation rather than being an optional operation, which as a result makes scrambling compatible with the last resort principle.
Keywords: Turkish language -- Syntax.; Grammar, Comparative and general.